Identification of the affected lower limb and unaffected side motor functions as determinants of activities of daily living performance in stroke patients using partial correlation analysis - Sato, Atsushi; Togashi, Yui; Ohashi, Takuro; Kasahara, Ryuichi; Tsuchiya, Kenji; Fujita, Takaaki; Otsuki, Koji; Yamamoto, Yuichi (Journal of Physical Therapy Science, 2015)
[Purpose] This study aimed to clarify the independent impact of the affected upper and lower limb, trunk, and unaffected side motor functions on activities of daily living in stroke patients using partial correlation analysis. [Subjects and Methods] This retrospective study included 77 stroke patients. Motor functions were assessed using the Stroke Impairment Assessment Set, and the activities of daily living performance was assessed using the Barthel index or Functional Independence Measure. Further, simple and partial correlation analyses were conducted between each motor function and activities of daily living parameter. [Results] Simple correlation analysis identified significant positive correlations for each pair. In contrast, partial correlation analysis only identified significant positive correlations between the affected lower limb or unaffected side functions and the Barthel index or Functional Independence Measure. This discrepancy between the two tests was explained by the significant interaction between the affected upper and lower limb functions and between the trunk and unaffected side functions. [Conclusion] The present study identified the affected lower limb and unaffected side motor functions as the major determinants of activities of daily living performance in stroke patients. These findings suggest that rehabilitation programs can be improved by targeting these areas.